Normal Blood Pressure and Different Factors Affecting it among Healthy School-Children - De, Arun Kumar; Chatterjee, Sukanta (Asian Journal of Medical Sciences, 2012)
Objective: To find out the normal range of blood pressure among school-children (aged 5-15 years) and the relationship of blood pressure with variables such as age and weight. Material & Methods: This is a school-based prospective cross-sectional study. Healthy school-children aged 5-15 years from primary and secondary schools in Kolkata were selected for the study. The individuals with any acute or chronic illnesses or the intersexes were excluded. Their age, weight, blood pressure and socioeconomic status were determined. Results: Blood pressure (both systolic and diastolic) showed almost upward linear relationship with age and weight in both boys and girls in the age group of 5-15 years. At 15 years, girls achieved higher blood pressure than boys did. The present study also showed that girls recorded higher blood pressure than boys in the weight range of 41-45 kg (For all “r” values, p <0.05). Conclusion: Blood pressure in children rises with age as well as with weight. Girls achieve higher blood pressure than boys do at the age of 15 years. DOI: http://dx.doi.org/10.3126/ajms.v2i3.5241 Asian Journal of Medical Sciences 2 (2011) 175-180